Performance, subversion in public school, cultural policies and dialogues (Revista de Ensino em Artes, Moda e Design, 2021)
In this article, I looked for relationships between subversion in arts, transgression as an element of performance, and aspects of local economies in culture inside the public school space, where I am a teacher. In the course of my doctorate, I draw parallels with some concepts of cultural policy in the current economic and political system, doing critical attention to art formatted in educational environments only as a product restricted to concealing absences and needs, the lack of access to expansions. In the aesthetic perceptions, which evoke for me a struggle against the simple reproducibility of artistic systems, with the students, I question for everybody about it. Benhamou, in the text The economy of culture, talks about cultural and public policy, so that they can build bridges between art, taken as a complete and total immanence of the individual and his idiosyncrasy - personal utopias, internal, ontological and subjective realities -, and the system of which the market is a part, with its monopolistic effects. In this way we can show a little about how to establish these relationships between subversive critical art, of ideological, moral, institutional, bureaucratic confrontation, with cultural policies that can revitalize spaces, generate local, social economies, and the generation of revenues in contact with the market aspect, without it totally absorbing the creative act, transforming it into a product without history, without life, “without soul”, unless that is the objective of the artistic production in question.
Keywords: Performance; Public school; Cultural policies